Plasmalogen in the brain: Effects on cognitive functions and behaviors attributable to its properties - Udagawa, Jun; Hino, Kodai (Brain research bulletin, 2022)
Ether phospholipid compositions are altered in the plasma or brain of patients with brain disorders, such as Alzheimer and Parkinson’s disease, including those with psychiatric disorders like schizophrenia and bipolar disorders. Notably, plasmenyl ethanolamine has a unique chemical structure, i.e., a vinyl-ether bond at the sn-1 position, which mainly links with polyunsaturated fatty acids (PUFAs) at the sn-2 position. Those characteristic moieties give plasmalogen molecules unique biophysical and chemical properties that modulate membrane trafficking, lipid rafts, intramolecular PUFA moieties, and oxidative states. Previous reports suggested that a deficiency in plasmenyl ethanolamine leads to disturbances of the myelin structure, synaptic neurotransmission and intracellular signaling, apoptosis of neurons, and neuroinflammation, accompanied by cognitive disturbances and aberrant behaviors like hyperactivity in mice. Therefore, this review summarizes the relationship between the biological functions of plasmalogen. We also proposed biophysical properties that alter brain phospholipid compositions related to aberrant behaviors and cognitive dysfunction. Finally, a brief review of possible remedial plasmalogen replacement therapies for neurological, psychiatric, and developmental disorders attributable to disturbed plasmalogen compositions in the organs and cells was conducted. •We review the correlation between plasmalogen and behavior.•Effect of plasmalogens on vesicle trafficking and signal transduction in the brain.•Aberrant behaviors led by alteration in the plasma and brain plasmalogen levels.•Improvement of brain plasmalogen compositions to alleviating brain disorders.